2020
DOI: 10.34172/ehem.2020.29
|View full text |Cite
|
Sign up to set email alerts
|

The performance of TiO2 /NaY-zeolite nanocomposite in photocatalytic degradation of Microcystin-LR from aqueous solutions: Optimization by response surface methodology (RSM)

Abstract: Background: Microcystin (MC) is a hepatotoxic and carcinogenic toxin that is generated by cyanotoxins which can have adverse effects on the human health. Therefore, it is very important to remove it from the environment. This study was performed to investigate the efficiency of titanium dioxide (TiO 2)/ NaY-zeolite (T/N-Z) nanocomposite for removal of MC-LR under ultraviolet light. Methods: In the present study, T/N-Z nanocomposite was synthesized using the hydrothermal method. Specification of the photocataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Fig. 3 , b, shows the structure of TiO 2 having a smooth surface and composed of aggregates with sharp edges in a similar finding by other studies [ 10 , 28 ]. The SEM images of the ion exchanged and the unmodified TiO 2 /BEA in Fig.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Fig. 3 , b, shows the structure of TiO 2 having a smooth surface and composed of aggregates with sharp edges in a similar finding by other studies [ 10 , 28 ]. The SEM images of the ion exchanged and the unmodified TiO 2 /BEA in Fig.…”
Section: Resultssupporting
confidence: 87%
“…The XRD diffraction patterns of TiO 2 showed peaks at 2θ = 25.2°, 36.98°, 48.4°, 54.9°, 62.7°, 68.8°, and 70.1° corresponding to the (101), (103), (200), (211), (204), (113), and (220) anatase phase planes, and 27.33°, 36°, and 41.2°, 44.1°, and 56.46° corresponding to (110), (101), (111), (210), and (220) for the rutile phase crystallographic planes based on (JCPDS 21–1272) and (JCPDS 21–1276) spectrum standards [ 25 ]. Accordingly, the sol-gel TiO 2 was observed in both anatase and rutile polymorphs consistent with those for solgel TiO 2 calcined under mild temperatures 200 °C < T < 550 °C [ 17 , 23 , [26] , [27] , [28] , [29] ]. The XRD diffraction patterns of the FeTZ catalysts and the unmodified 60TZ photocatalyst possessed very low crystallinity as compared to TiO 2 .…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Thus, generation of hydroxyl radicals on the surface of catalyst for degradation of metronidazole is limited. Also, with increasing metronidazole concentration, the radiation photons, which react with catalyst surface, are prevented and screened off, therefore, the production of hydroxyl radicals is delayed and the degradation of metronidazole is decreased (8,(41)(42)(43)(44)(45)(46). Sobana et al investigated photocatalytic degradation of acid red 18 by ZnO nanoparticles and found that by increasing the concentration of acid red 18, the removal efficiency decreased, which is consistent with the results of this study (47).…”
Section: Discussionsupporting
confidence: 89%
“…But today, researchers are increasingly using efficient methods, which are economically sustainable technologies for treating colored effluents (18)(19)(20). Today, the photocatalyst process is used as a simple and efficient method to remove organic pollutants and dyes from industrial effluents and has been shown to play a significant role in environmental control by decomposing organic pollutants (21)(22)(23). The photocatalytic technique is superior to traditional purification techniques.…”
Section: Introductionmentioning
confidence: 99%